The Impact of Negative Publicity on Police Self-legitimacy. (2nd January 2017) - Nix, Justin; Wolfe, Scott E.
Abstract : High-profile events involving police use of force in various cities throughout the US and internationally have garnered enormous media coverage and demonstrated the importance of police-community relations. To date little empirical attention has focused on how such events may negatively impact police officers. Using survey data from 567 officers, this study considers whether perceptions of negative publicity are adversely related to officers' sense of self-legitimacy (i.e. the confidence they have in their authority). Findings revealed officers who felt less motivated as a result of negative publicity expressed less self-legitimacy. However, the degree to which officers felt their job had become more dangerous as a result of negative publicity was not significantly related to self-legitimacy. These findings increase our understanding of the sources of self-legitimacy and reveal that negative publicity surrounding law enforcement presents a unique challenge to officers' confidence in their authority, which can have important implications for the community.